Дистрибуция древнеанглийских дифтонгов преломления - Забулене, Лайма (Kalbotyra, 1988)
The consonant which caused breaking of the short vowels /æ. e i/ most readily was h, but l and r also caused the change when they were followed by another consonant. The most productive clusters in this respect were rn, rd and ld. It should be noted that the dorsal consonant h exerted a breaking influence on both short and long front vowels.The distribution of OE breaking diphthongs can be characterized by two positions: initial and medial. The diphthongs resulting from breaking displayed different field of distribution. The diphthongs /ē̌a/ are represented much wider in comparison with /ē̌o/ and /ī̌o/.